As lutas entre o dever de memória e o poder do esquecimento: avaliação do processo de tombamento da Casa Frei Tito de Alencar - Monteiro, Rosana Carolina Maia (2022)
To understand the construction of cultural heritage is necessary to start from the premise that it is a product of a field of conflicts, which involves force and power and, from that on, intentionally, the formation of some memories and the obliteration of others occur, filling the interests of a certain social level (as well as the Estate’s), which is subtle for most of the population throughout history. Thus, is necessary a process of the project’s denaturalization and invisibility of memories perpetrated by patrimonial public policies, understanding that patrimony is a social construct. Through this concept, this dissertation has the objective of evaluating the process of patrimonialization, through the preservation tool of Frei Tito de Alencar’s House, following law number 9.347/2008. The act of property listing of the cited historic home happened temporarily in 2011 (process number 9.0594/2011), ruled by Municipal Decree number 12.843, from July 22nd, 2011. We sought to understand, through the social subjects involved in the politics, interests, values, and aspects that follow through this act, how the conservation of this cultural property from Fortaleza supports the preservation of Frei Tito De Alencar Lima’s memory, a character from Ceará, directly linked to the fight for democracy, in a historical period marked by the obscurantism in the country, which was the civil-military dictatorship from 1964 to 1985. To comprehend in a more meaningful way the questions involved in the preservation process of Frei Tito de Alencar’s House and how the policy of patrimonial preservation is experienced in practice, we chose a qualitative approach based on Lejano’s (2012) post-constructivist paradigm. The used methodological procedures were the theoretical framework and documental research, in addition to the application of questionnaires to the social subjects involved with the topic of preservation of cultural heritage in Fortaleza. The fact is that the current moment is going through a deconstruction in the field of cultural heritage public policies, especially at the federal level. Furthermore, there is currently denialism related to that historical period of our country, in addition to the praise of torturers responsible for various crimes, which makes the reflection on this recent past of our history increasingly urgent. The results of this research reinforce that the process of property listing of cultural heritage is vital to its preservation; however, it cannot be the only option to act in isolation in favor of the listed property's preservation. In other words, the combination of the precautionary instrument together with environmental education and how the use of the listed property can protect Frei Tito de Alencar’s House, a cultural heritage from Fortaleza. Facing these discoveries and the meaning of Frei Tito’s memory and what it represents to our society, mainly the preservation of that cultural heritage is recognized as crucial and pedagogical.